Leukotriene D4 receptor antagonist montelukast alleviates water avoidance stress-induced degeneration of the gastrointestinal mucosa - ERCAN, FERİHA; ÇETİNEL, ŞULE (ELSEVIER SCI LTD, 2008)
We investigated the role of montelukast (ML), a cysteinyl leukotriene-1 receptor antagonist, on the water avoidance stress (WAS)induced degeneration of the rat gastric, ileal and colonic mucosa. One group of Wistar albino rats were exposed to chronic WAS (WAS group) 2 h daily for 5 days. Another group was administered ML (10 mg/kg; i.p.; WAS + ML group) following every WAS exposure for 5 days. Control rats were injected with the vehicle solution only. The stomach, ileum and colon were dissected and investigated for histopathological changes with a light microscope as well as for topographical changes with a scanning electron microscope. The levels of malondialdehyde (MDA, a biomarker of oxidative damage) and glutathione (GSH, a biomarker of protective oxidative injury) were also determined in all dissected tissues. In the WAS group, the stomach epithelium showed ulceration in some areas, dilatations of the gastric glands, degeneration of gastric glandular cells, and prominent congestion of the capillaries. In a similar fashion, degenerated epithelium and severe vascular congestions were observed in the ileum and colon. In all the tissues dense inflammatory cell infiltration and mast cell degranulation in mucosa were observed. The levels of MDA were significantly increased whereas those of GSH were significantly decreased in all test tissues in the WAS group compared to the control group. The morphology of gastric, ileal and colonic mucosa in WAS + ML group showed a significant amelioration showing a reduction in inflammatory cell infiltration and mast cell degranulation. Increased NIDA and decreased GSH levels in the WAS group were also ameliorated with ML treatment. Based on the results, ML supplement seems attenuated inflammatory effects of WAS induction in gastrointestinal mucosa. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: BLOOD-FLOW; BLOCKER MONTELUKAST; EPITHELIAL BARRIER; COLD-RESTRAINT; FREE-RADICALS; RAT; INJURY; INFLAMMATION; INHIBITION; MECHANISMS